Pahljača kot ceremonialni in religijski predmet na Japonskem - Visočnik, Nataša (Poligrafi, 2022)
Far from being mere cooling devices, in Japan, hand fans play an important role in social life, customs and artistic development. related to various aspects of Japanese culture, they can be employed as dance props, tools for transmitting messages or telegraphing wealth and social status, a canvas for artistic expression, and an object associated with ceremonial and religious purposes. The use of hand fans in religious and ritual practice is historically well established. The fan was held in the hand or placed in front of oneself during prayers to the gods; it would serve either as a symbolic manifestation of divinity or merely as a tool for praying to the gods; it was also used as a gift on ceremonial and special occasions, such as weddings, funerals, and tea ceremonies. To facilitate the understanding of the role of hand fan in Japanese society, and the religious sphere in particular, the paper provides insight into the historical development of this device, presenting its various types and forms and their usages in ceremonial and religious events. In an investigation of Slovenian museum collections of artefacts of asian provenance, several hand fans were found that likely resemble those used for ceremonial purposes and in religious life in Japan. They are presented and analysed herein ? their constructions, forms, dimensions and styles studied and classified based on the relevant literature ? and compared to the hand fans used in Japanese religious rituals.
Keywords: ceremonial objects; hand fans; Japanese religions; japonske religije; museum collections; muzejske zbirke; obredni predmeti; pahljače; religijski predmeti; religious objects; simbolika pahljač; symbolism of hand fans